Pengaruh Dispositional Mindfulness Terhadap Regulasi Emosi Mahasiswa Yang Sedang Menyelesaikan Skripsi - Asti Maysaroh; Dhevy Puswiartika; Munifah Munifah; Azam Arifyadi (LPPM Institut Pendidikan Nusantara Global, 2026)
The process of completing a thesis often generates psychological pressure that may affect students’ ability to regulate their emotions. Dispositional mindfulness is considered an important factor that may support emotion regulation. This study aimed to examine the level of dispositional mindfulness, the level of emotion regulation, and the effect of dispositional mindfulness on emotion regulation among students completing their thesis. A quantitative approach with simple linear regression analysis was employed. The participants were 100 final-year students from the Faculty of Teacher Training and Education. Data were collected using dispositional mindfulness and emotion regulation scales. The results showed that dispositional mindfulness was categorized as high in 82% of participants, while emotion regulation was categorized as high in 51% of participants. Furthermore, dispositional mindfulness had a positive and significant effect on emotion regulation (p < 0.001), contributing 21.9% of the variance. These findings indicate that higher dispositional mindfulness is associated with better emotion regulation among students completing their thesis.